Estimation of Socioeconomic Status and Rainwater Consumption in Ibadan Metropolis, Nigeria - Kehinde Paul Adeosun; Bolarin Titus Omonona (Journal of Agricultural Extension, 2021)
The study examined the influence of socioeconomic factors on the utilization of rainwater among households in Ibadan metropolis, Oyo-State, Nigeria. Primary data were collected through a semi-structured questionnaire from 126 randomly selected households. A double-hurdle estimation model using Ordered Probit with sample selection and Probit-Truncated Negative Binomial model were  used. The findings of the study indicated that the sex of the household head, marital status, female household size, education, occupation, size of rainwater collection material, root-top structure are important determinants of extent of rainwater usage. Male headed household, education, and size of rainwater collection material positively and significantly influenced the frequency of rainwater usage, while sex and occupation inversely and significantly influenced the frequency of rainwater usage. Likewise, education, size of rainwater collection material, roof-top structure positively associated with the number of uses of rainwater. The study concludes that the socioeconomic status of the household is an important determining factor in the harvesting and utilization of rainwater. Therefore, policy on rainwater harvesting and usage should consider the significant socioeconomic factors of the household as a starting point in the decision process.